Local and Community Driven Development : Moving to Scale in Theory and Practice - Binswanger-Mkhize, Hans P.; De Regt, Jacomina P.; Spector, Stephen (World Bank, 2012)
Services are failing poor urban and rural people in the developing world, and poverty remains concentrated in rural areas and urban slums. This state of affairs prevails despite prolonged efforts by many governments to improve rural and urban services and development programs. This book focuses on how communities and local governments can be empowered to contribute to their own development and, in the process, improve infrastructure, governance, services, and economic and social development, that is, ultimately, the broad range of activities for sustainable poverty reduction. Countries and their development partners have been trying to involve communities and local governments in their own development since the end of Second World War, when the first colonies gained independence in South Asia. Pioneers in both India and Bangladesh (then a part of Pakistan) developed a clear vision of how it will be done: local development should be planned and managed by local citizens, their communities, and their local governments within a clearly defined decentralized framework that devolves real power and resources to local governments and communities. Capacity support will be provided by technical institutions and sectors and nongovernmental institutions.